Network Meta-Analysis and Trial Sequential Analysis of Randomised Controlled Trials Comparing Robotic, Laparoscopic, and Open Pancreatoduodenectomy - Nejo Joseph, MBChB; Chris Varghese, MBChB; James Lucocq, MBChB; Matthew J. McGuinness, MBChB; Samuel Tingle, MBChB; Giovanni Marchegiani, PhD; Kjetil Soreide, PhD; Mohammed Abu-Hilal; Jas Samra; Marc Besselink, PhD; Steve White; Sanjay Pandanaboyana, FRCS (Annals of Surgery Open)
Background:. The use of minimally invasive (laparoscopic and robotic) pancreatoduodenectomy (PD) is being increasingly adopted despite the lack of hard evidence to support its utilisation. With recent randomised controlled trials (RCTs) comparing open pancreatoduodenectomy (OPD) with robotic or laparoscopic pancreatoduodenectomy (RPD or LPD), we undertook a network meta-analysis (NMA) comparing all 3 approaches to evaluate comparative outcomes. Methods:. A systematic search of MEDLINE, EMBASE, and Cochrane CENTRAL was conducted up to May 2024 and relevant RCTs were identified. A random-effects meta-analysis and trial sequential analysis (TSA) were conducted for primary outcomes, followed by a Bayesian NMA of length of stay (LOS), duration of surgery, intraoperative blood loss, and pancreas resection-related outcomes Results:. Seven RCTs involving 1336 patients were included, 5 investigating LPD compared with OPD and 2 RPD to OPD. Pairwise meta-analysis indicated that LPD was associated with shorter hospital stay (mean difference [MD], −1.39; 95% confidence interval [CI], −2.33 to −0.45) and lower intraoperative blood loss compared with OPD (MD, −131; 95% CI, −146 to −117). However, LPD was associated with significantly longer operative duration (MD, 39.5; 95% CI, 34–45). TSA confirmed the robustness of the positive and negative findings on pairwise meta-analysis. In comparison, there were no significant differences between RPD and OPD in pairwise meta-analysis, which could not be confirmed by TSA. Network meta-analysis tended to favour LPD in most outcome parameters including LOS, duration of surgery, and pancreas resection-related outcomes. Conclusions:. The current RCT evidence suggests potential better outcomes in LPD in comparison with RPD and OPD. However, few studies demonstrated robust statistical significance in outcome measures, suggesting an underpowered evidence base and possible selection bias. Hence, with current equivocal data, there is a need for ongoing RCTs to validate the role of minimally invasive approaches in PD.